Features of retinal bioelectrical activity in the fellow eye of patients with rhegmatogenous retinal detachment associated with choroidal detachment (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To determine, based on full-field electroretinogram (ffERG) data, the features of bioelectrical activity in the fellow eye of moderate and high myopes with rhegmatogenous retinal detachment (RRD) associated with choroidal detachment (CD) (RRD+CD).Material and Methods: Fifty-two fellow eyes were examined three months after surgery for RRD in the first eye (32 eyes with RRD only and 20 eyes with RRD+CD). A group of 14 normal individuals (28 eyes) was used as a control group. Patients underwent ophthalmological examination and International Society for Clinical Electrophysiology of Vision (ISCEV) ffERG testing.Results: The severity of myopia and the presence of CD in the affected eye were found to be the factors that influenced the dark-adapted (DA) 0.01 ERG b-wave amplitude (F = 3.83, р = 0.01 and F = 5.0, р = 0.03, respectively) and DA 3.0 ERG b-wave amplitude (F = 4.65, р = 0.012 and F = 9.18, р = 0.005, respectively). In the fellow eye of RRD+CD patients, light-adapted (LA) 3.0 ERG a-wave and b-wave peak times were by 14% longer (р = 0.005), and by 12.3% longer (р < 0.05), respectively, compared to the controls. The presence of CD in the affected eye was found to be a factor that influenced the LA 3.0 ERG a-wave peak time (F = 10.2, р = 0.003): the peak time in the fellow eye for high myopes with RRD+CD was by 19% longer than for those with RRD only. The presence of myopia in the affected eye was found to be a factor that influenced the LA 3.0 ERG b-wave amplitude (F = 3.02, р = 0.042): compared to the controls, the b-wave amplitude in the fellow eye was reduced by 32.5% (р = 0.01) for high myopes with RRD only, and by 40% (р = 0.005) for those with RRD+CD.Conclusion: We found substantial difference between groups of myopes with RRD+CD and groups of myopes with RRD only in terms of electrical activity of the peripheral retina (the rod photoreceptor layer and layers of inner retinal bipolar cells) in the fellow eye. Based on the findings of our study of the fellow eye in patients with a severity of myopia in the fellow eye being similar to that in the first eye, it may be hypothesized that CD develops in RRD patients with more severe abnormalities in ERG.
Keywords: retinal detachment; choroidal detachment; electroretinography; myopia; retinal degeneration